Using Social Media to Conduct Outreach and Recruitment for Expanded Newborn Screening - Guillory, Jamie; Jordan, Alyssa; Paquin, Ryan S.; Pikowski, Jessica; McInnis, Stephanie; Anakaraonye, Amarachi; Peay, Holly L.; Lewis, Megan A. (Frontiers in Communication, 2020)
Social media platforms are becoming a key resource for health research and program delivery. These platforms offer multiple avenues to engage diverse populations using organic and paid content. Outreach to and recruitment of participants into population-based studies are important features of these platforms. We examine the potential benefit of social media for recruitment into Early Check, a statewide research program in North Carolina offering expanded newborn screening for two rare conditions that are not currently part of regular newborn screening in the state. In addition to using traditional outreach strategies—such as direct mail—we implemented social media strategies, including organic content posted to the Early Check Facebook and Twitter accounts and paid advertising on Facebook and Instagram between March and September 2019. During that time, we posted 95 organic posts on Facebook, which garnered 50,895 impressions and 373 link clicks to visit the sign-up portal and 94 posts on Twitter, with 46,638 impressions and 78 portal link clicks. We ran five paid social media ad campaigns using Facebook and Instagram, with 1,042,346 impressions total and 6,918 link clicks. The paid and organic strategies that resulted in the largest number of link clicks on ads featured images of pregnant women and relevant facts and content on key dates that might be motivating to pregnant women or new mothers, such as the first day of spring. In total, 3,298 women completed the study screener and were eligible to enroll (17.5% from paid social, 82.5% from other sources) and 2,375 enrolled (9.9% paid social, 90.1% other sources). A time series regression revealed that, on average, approximately 15 women enrolled in Early Check per day, excluding the effect of paid ads. On average, we observed 3.5 additional daily enrollments with paid social media ads, with 7 additional women enrolled in Early Check for every 2 days that we ran ads. Early Check is the first study to use paid and organic social media content to complement traditional outreach strategies in a recruitment effort focused on accelerating understanding of rare diseases and treatments for newborns.